Laser-plasma interaction in direct-drive inertial confinement fusion. (May 2016) - Myatt, J F; Shaw, J; Goncharov, V N; Zhang, J; Maximov, A V; Short, R W; Follett, R K; Seka, W; Edgell, D H; Froula, D H
Abstract: Hot electrons generated by the two-plasmon-decay instability in direct-drive targets are a preheat concern. A mitigation strategy that employs a layered ablator [V. N. Goncharov et al., Phys. Plasmas 21, 056315 (2014)] has been investigated both numerically and experimentally. The numerical simulations described here predict reduced hot-electron production compared with similar targets using either a solid CH or Be ablator. These findings are shown to be consistent with experimental observations